2023
DOI: 10.1017/s0954579422001481
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors of child behavioral health across developmental stages

Abstract: This study examines the relative influence of environmental contexts (family, school, neighborhood) on child behavioral health at ages 3, 5, 9, and 15 years. Path analysis was conducted on a sample of 4,898 urban children from a longitudinal dataset called the Fragile Families and Child Wellbeing Study. Child physical abuse, emotional abuse, maternal depression, substance use, neighborhood social cohesion, neighborhood poverty, school connectedness, and peer bullying had concurrent relationships with child beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Wiggins et al, 2015;Y. Xu et al, 2020;Yoon et al, 2023) Child-reported depressive symptoms at 15 years We used items of the Center for Epidemiologic Studies Depression Scale (Radloff, 1991) scale to assess self-reported depressive symptoms. The scale consisted of 5 items, with questions such as "I feel I cannot shake off the blues, even with help from my family and my friends'', "I feel sad", "I feel depressed".…”
Section: Participantsmentioning
confidence: 99%
“…Wiggins et al, 2015;Y. Xu et al, 2020;Yoon et al, 2023) Child-reported depressive symptoms at 15 years We used items of the Center for Epidemiologic Studies Depression Scale (Radloff, 1991) scale to assess self-reported depressive symptoms. The scale consisted of 5 items, with questions such as "I feel I cannot shake off the blues, even with help from my family and my friends'', "I feel sad", "I feel depressed".…”
Section: Participantsmentioning
confidence: 99%